Los Angeles County Juvenile Justice Crime Prevention Act Fiscal Year 2011-2012 Report - Fain, Terry (RAND Corporation, 2013)
This annual report for the California Board of State and Community Corrections measures the success of Juvenile Justice Crime Prevention Act programs and initiatives for six state-mandated outcome measures (successful completion of probation, arrests, probation violations, incarcerations, successful completion of restitution, and successful completion of community service) and county-required supplemental measures.